Relevansi Kurikulum Program Studi Hukum Terhadap Kompetensi Mahasiswa Lulusan Program Studi Hukum UIN Sumatera Utara - Zaid Alfauza Marpaung; M. Rizal; Shiddiq Al-Hakimi (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
The influence of globalisation gacorwin requires study programmes to continuously conduct self-evaluation in order to maintain the relevance of their academic programmes to the development of science and technology, the needs of society, and the demands of the world of work. Problems often arise when study programmes are unable to identify and evaluate themselves in responding to developments in science and technology, the needs of the world of work, and the expectations of graduate users. As a result, curriculum development is not systematic, holistic, and complex. This research aims to analyse the relevance of the curriculum of UIN North Sumatera Law Study Program to the competencies of graduates. The method used in this research is qualitative by collecting primary and secondary data sources which are then analysed. The results showed that the curriculum development of UIN North Sumatera Legal Studies Programme is relevant to the competence of graduates. This can be seen from the structure and distribution of courses that support graduate learning outcomes. The learning outcomes of graduates of the UIN North Sumatera Legal Studies Programme are determined on the profile of graduates as judges, prosecutors, advocates, mediators, legal consultants, and arbitrators who have good personalities, are knowledgeable and up-to-date, and are able to carry out general duties as legal practitioners and special duties in accordance with Islamic ethics, science, and expertise. This research gacorwin has implications for curriculum evaluation to produce an up-to-date curriculum according to the needs of society.